Drugs for spontaneous coronary dissection: a few untrusted options - Ilic, Ivan; Radunovic, Anja; Timcic, Stefan; Odanovic, Natalija; Radoicic, Dragana; Dukuljev, Natasa; Krljanac, Gordana; Otasevic, Petar; Apostolovic, Svetlana (Frontiers in Cardiovascular Medicine, 2023)
Spontaneous coronary artery dissection (SCAD) is an unusual cause of acute coronary syndrome that is often overlooked, misdiagnosed, and maltreated. Medical treatment poses a significant challenge because of lack of randomized studies to guide treatment. Initial clinical presentation should guide medical and interventional management. Fibrinolytic agents and anticoagulants should be avoided because they could favor hematoma propagation. Antiplatelet therapy should be prescribed in patients with SCAD and in most of them it should be dual (DAPT) consisting of aspirin and clopidogrel, while potent P2Y12 inhibitors, ticagrelor and prasugrel should be avoided. If stent was used DAPT should be continued for 12 months. Aspirin only, can be an option for patients without "high risk" angiographic featuresthrombus burden, critical stenosis, decreased coronary flow. Beta blocking (BB) agents should be used to prevent recurrence of SCAD. There is a general agreement that angiotensin-converting enzyme (ACE) inhibitors, angiotensin-receptor blockers (ARB), mineralocorticoid antagonists and loop diuretics should be used in patients with SCAD experiencing the symptoms of heart failure and decrease in LVEF below 50%.Although without firm evidence, statins can be used in SCAD due to their pleiotropic properties. The results of randomized trial on use of BB and statins are awaited. Aggregation of data from national registries might point out truly beneficial medications for patients with SCAD.